2008
DOI: 10.1111/j.1365-2141.2008.07263.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of minimal residual disease in multiple myeloma patients by fluorescent‐polymerase chain reaction: the prognostic impact of achieving molecular response

Abstract: Summary This study aimed to standardize a simple molecular method for evaluating the response to treatment in multiple myeloma (MM) patients after high dose chemotherapy. Fifty three patients enrolled in the GEM2000 protocol were studied for minimal residual disease (MRD) using both fluorescent‐polymerase chain reaction (F‐PCR) and flow cytometry. Most patients had achieved complete remission or very good response after autologous stem cell transplantation. The molecular analysis of immunoglobulin gene rearran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 31 publications
(38 reference statements)
1
32
0
Order By: Relevance
“…As outlined previously, [22][23][24][25][26] the GEM2000 protocol was active from January 2000 to February 2005 (ClinicalTrials.gov: NCT00560053); patients aged less than 70 years with symptomatic, newly diagnosed MM who were candidates for HDT/SCT were included. Patients received induction therapy comprising six alternating cycles of VBMCP/VBAD chemotherapy, with peripheral blood stem cell collection after cycle 4 using granulocyte colony-stimulating factor 16-24 µg/kg daily for 5 days for priming.…”
Section: Therapeutic Programmentioning
confidence: 99%
“…As outlined previously, [22][23][24][25][26] the GEM2000 protocol was active from January 2000 to February 2005 (ClinicalTrials.gov: NCT00560053); patients aged less than 70 years with symptomatic, newly diagnosed MM who were candidates for HDT/SCT were included. Patients received induction therapy comprising six alternating cycles of VBMCP/VBAD chemotherapy, with peripheral blood stem cell collection after cycle 4 using granulocyte colony-stimulating factor 16-24 µg/kg daily for 5 days for priming.…”
Section: Therapeutic Programmentioning
confidence: 99%
“…38 As an alternative, ASO realtime quantitative PCR provides an accurate quantification of residual disease, thus overcoming the problem. Several reports using this technique have been published, showing effective outcome discrimination in the transplant setting 29,[39][40][41][42][43] (Table 5). …”
Section: Novel Methods To Measure Mrdmentioning
confidence: 99%
“…There have been multiple studies comparing these techniques (Table 6). 40,44,45 In three consecutive trials, Puig et al 46 analyzed differences in ASO-PCR and MFC in 170 patients that had achieved at least a PR following treatment. MRD negativity was defined as ⩽ 10 − 4 .…”
Section: Comparison Of Mfc and Aso-pcrmentioning
confidence: 99%
“…[5][6][7] Despite this level of response, studies have shown that the vast majority of patients have residual tumor cells that can be detected with a variety of sensitive techniques. [8][9][10][11] Several studies have demonstrated a consistent improvement in progression-free survival (PFS) with attainment of CR, but its impact on overall survival (OS) has been varied. 12,13 The impact of depth of response on PFS is not surprising, as that could be a mere reflection of the time taken for the clone to grow to a measurable level following a more effective eradication.…”
mentioning
confidence: 99%
“…The current results, similar to a previous study, clearly demonstrate equivalent ability of the two techniques to detect residual disease, but crucial differences in terms of feasibility. 11 Two issues remain critical; the inability to obtain successful primers in up to a third of the patients, and the absolute requirement for a baseline sample hampers universal adaptation of this technique. These, along with the required expertise and the more universal access to flow cytometry in most of hematology laboratories, makes flow cytometry the method of choice today, and increasing ability to interrogate millions of cells in a short time and increasing number of markers that can be accommodated at a time will lead to increasing sensitivity, specificity and ease of use of this technique.…”
mentioning
confidence: 99%